The impact of information risk and market stress on institutional trading: New evidence through the lens of a simulated herd model - Christopher K. Boortz; Simon Jurkatis; Stephanie Kremer; Dieter Nautz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper sheds new light on the impact of information risk and market stress on herding of institutional traders from both, a theoretical and an empirical perspective. Using numerical simulations of a herd model, we show that buy and sell herding intensity should increase with information risk. Market stress should affect herding asymmetrically: while there is more sell herding when the market becomes more pessimistic and more uncertain, buy herding intensity should decrease. We test these predictions using intra-day herding measures based on high-frequent, investor-specific trading data of all institutional investors in the German stock market. The evidence provides strong support for an increasing effect of information risk on herding intensity on an intra-day basis. However, in contrast to the simulation results empirical herding measures indicate that buy herding has even slightly increased, not decreased, during the recent crisis period.
Keywords: G11; G24; C23; 330